2011
DOI: 10.2105/ajph.2010.300027
|View full text |Cite
|
Sign up to set email alerts
|

Health Advocacy Organizations and the Pharmaceutical Industry: An Analysis of Disclosure Practices

Abstract: Health advocacy organizations (HAOs) are influential stakeholders in health policy. Although their advocacy tends to closely correspond with the pharmaceutical industry's marketing aims, the financial relationships between HAOs and the pharmaceutical industry have rarely been analyzed. We used Eli Lilly and Company's grant registry to examine its grant-giving policies. We also examined HAO Web sites to determine their grant-disclosure patterns. Only 25% of HAOs that received Lilly grants acknowledged Lilly's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 5 publications
1
48
0
Order By: Relevance
“…This has led some sociologists to investigate ways in which industrial corporations have set about influencing patient advocacy in a number of countries (e.g. O'Donovan 2007; Rothman et al 2011). Though few suggest that the advocacy agenda has been wholly captured, a lack of transparency regarding the extent of sponsorship in each of the countries seems no longer to be in doubt.…”
Section: S Blumementioning
confidence: 99%
“…This has led some sociologists to investigate ways in which industrial corporations have set about influencing patient advocacy in a number of countries (e.g. O'Donovan 2007; Rothman et al 2011). Though few suggest that the advocacy agenda has been wholly captured, a lack of transparency regarding the extent of sponsorship in each of the countries seems no longer to be in doubt.…”
Section: S Blumementioning
confidence: 99%
“…However, recently, many people (Colombo et al 2012;Mosconi and Colombo 2010;Rothman et al 2011), have denounced the opacity of patient association funding, which comes partly from industries. To clarify this point, let us recall that, when a patients' organization grows up and augments its influence, it needs to employ full time administrators, who quickly establish a kind of bureaucracy, whose aims are a long way away from patients' interests: quite naturally, these administrators become mainly occupied with the influence of their organization, which justifies their employment and satisfies their personal ambitions.…”
Section: Forty Years Latermentioning
confidence: 99%
“…The industry has also financed criticism of particular reviews by groups that advocate for patients with particular diseases or who suffer chronic pain (Craig 2002; Fox 2010a; Moynihan 2003; Rothman et al 2011). Reviews that found insufficient evidence of the effectiveness of some interventions often dismayed these groups (Drug Effectiveness Review Project 2004–2009; Fox 2010a; Hawkes 2009).…”
Section: Antagonism To Systematic Reviews In the Health Sectormentioning
confidence: 99%